AUDIT TERHADAP SUMBER DAYA MANUSIA SEBAGAI INTELLECTUAL PROPERTY - Erica, Denny (www.bsi.ac.id, 2016)
Human resources is one of the components that are relatively difficult to be audited by the management company, because the human resources function as regulators, implementers, and control or supervision. So from that audit of human resource development should be able to provide an independent overview in order to encourage the effectiveness and synergies for all the activities of both the holistic balance to proportion the role of HRD in each work unit. Data collection methods used in this study using literature associated with some methods in conducting an audit of human resources, which can be used as the basis of ongoing research. Usefulness of information obtained from the audit of the human resources, the management company can conduct an internal evaluation into the enterprise to all units of human resources as a form of business in order to improve human resources to be much better controlled than before. In addition, the results of the audit of human resources management can help companies to identify the problems faced by each individual employee each work unit were different. And in the end by improving the quality of human resources and the quality of the work that is much better, can create an atmosphere of work and scope of a healthy work culture in supporting the development of the company to be more prepared and resilient to be able to compete with other companies. So from that human resources can be regarded as a form of Intellectual Property. Keywords: Audit, Human Resources, Intellectual Property.